A metabolomic approach to investigate effects of ocean acidification on a polar microalga Chlorella sp. - Tan, Yong Hao; Lim, Phaik Eem; Beardall, John; Poong, Sze Wan; Phang, Siew Moi (Elsevier, 2019)
Ocean acidification, due to increased levels of anthropogenic carbon dioxide, is known to affect the physiology and growth of marine phytoplankton, especially in polar regions. However, the effect of acidification or carbonation on cellular metabolism in polar marine phytoplankton still remains an open question. There is some evidence that small chlorophytes may benefit more than other taxa of phytoplankton. To understand further how green polar picoplankton could acclimate to high oceanic CO2, studies were conducted on an Antarctic Chlorella sp. Chlorella sp. maintained its growth rate (∼0.180 d-1), photosynthetic quantum yield (Fv/Fm = ∼0.69) and chlorophyll a (0.145 fg cell-1) and carotenoid (0.06 fg cell-1) contents under high CO2, while maximum rates of electron transport decreased and non-photochemical quenching increased under elevated CO2. GCMS-based metabolomic analysis reveal that this polar Chlorella strain modulated the levels of metabolites associated with energy, amino acid, fatty acid and carbohydrate production, which could favour its survival in an increasingly acidified ocean. © 2019 Elsevier B.V.